A ten year retrospective study of the aetiology and outcome of crescentic glomerulonephritis in children presenting to the Red Cross Children's Hospital, Cape Town, South Africa - Mwaba, Chisambo (Department of Paediatrics and Child Health, 2017)
Background: Crescentic glomerulonephritis represents the extreme end on the spectrum of glomerular injury. It can result from a wide range of disease conditions and clinically is marked by a rapid deterioration in renal function over days, weeks or months. Although rare, crescentic glomerulonephritis is an important entity to recognize because prompt treatment can improve patient outcomes significantly. Literature on the prevalence, clinical presentation, aetiology and outcome of histologically proven crescentic glomerulonephritis among children, in Africa, is scanty. Most of what is known about this entity is extrapolated from adult studies and from paediatric studies that have for the most part been conducted outside the African continent. Objective: This study was conducted in order to determine the incidence, clinical presentation, aetiology and outcome of histologically proven crescentic glomerulonephritis in children presenting to the Red Cross Children's Hospital, Cape Town, South Africa. Methods: This was a retrospective folder review in which the renal biopsy records of children less than 18 years old who had had native kidney biopsies performed between 2004 and July 2015 at the Red Cross Children's Hospital were reviewed. The clinical notes of patients found to have been diagnosed with crescentic glomerulonephritis were traced so as to extract demographic and clinical information which was then recorded onto the study data sheet. No attempt to contact patients or their families was made. Data analysis with regard to the incidence, the clinical features and the outcome of crescentic glomerulonephritis was done using SPSS version 22. Results: A total of 470 native kidney biopsies were performed in the period under review. Of these, 24 had crescentic glomerulonephritis, accounting for an incidence of 5.1 %. The sub-types of crescentic glomerulonephritis were immune-complex in 19 (80%), Pauci-immune in 2 (8 %), unspecified type in 3 (12 %) and no child had the anti-glomerular basement membrane subtype. The underlying aetiology of the immune complex sub-type was post-infectious in 11(57.9%), idiopathic in 4(21%), HSP/IgA nephropathy in 2 (10.5%), SLE in 1 (5.3%) and mesangiocapillary glomerulonephritis in 1(5.3%). Fourteen of the subjects were male thus giving a male to female ratio of 1.4 while the mean age of the children was 8.3 [range- 1 to 14 years]. The commonest clinical features were hypertension (90%), nephrotic range proteinuria (80%), macroscopic haematuria (57%), oedema (94%) and anaemia (88%). None of these had a statistically significant association to the renal outcome. Ten (77%) out of the 13 children with crescentic glomerulonephritis who were followed up for more than a year were found to have either died, had residual renal dysfunction or been transplanted at the last clinical contact. Conclusion: Crescentic glomerulonephritis was diagnosed in 5.1% of paediatric native renal biopsies which is consistent with what has been reported elsewhere. Unlike reports from other geographical areas the vast majority (80%) of the cases had immune-complex glomerulonephritis with a suspected post-infectious aetiology in over half of these. Similar to earlier reports from South Africa the outcome was poor in most (77%) of the patients. Further research is required to characterise the factors that make post-infectious glomerulonephritis particularly severe in this population.